Modeling stationary and moving pebbles in a pebble bed reactor. (June 2015) - Zhao, Xiang; Montgomery, Trent; Zhang, Sijun
Highlights: The stationary and moving pebbles in a PBR are numerically studied by DEM. The packing structure of stationary pebbles is simulated by a filling process. The packing structural properties are obtained and analyzed. The dynamic behavior of pebbles is predicted and discussed. Abstract: This paper presents a numerical study of the stationary and moving pebbles in a pebble bed reactor (PBR) by means of discrete element method (DEM). The packing structure of stationary pebbles is simulated by a filling process that terminates with the settling of the pebbles into a PBR. The packing structural properties are obtained and analyzed. Subsequently, when the outlet of the PBR is opened during the operation of the PBR, the stationary pebbles start to flow downward and are removed at the bottom of the PBR. The dynamic behavior of pebbles is predicted and discussed. Our results indicate the DEM can offer both macroscopic and microscopic information for PBR design calculations and safety assessment.